2022-RA-711-ESGO Association of PET-CT tumor metabolic metrics and intraepithelial and stromal tumor-infiltrating lymphocytes in locally advanced cervical cancer prior to concurrent chemo-radiotherapy. (20th October 2022) - Martinez, Alejandra; Del, Mathilde; Illac, Claire; Angeles, Martina Aida; Ducassou, Anne; Bétrian, Sarah; Bataillon, Guillaume; Ferron, Gwénaël; Motton, Stéphanie; Lusque, Amélie; Gabiache, Erwan
Abstract : Introduction/Background: Literature data suggests an association between PET/CT metabolic metrics and tumor microenvironment in several malignancies, and a potential role of PET/CT to monitor response to immunotherapy. The aim of the study is to evaluate the correlation between PET/CT tumor metabolic metrics and tumor-infiltrating lymphocytes (TILs) infiltration in locally advanced cervical cancer (LACC) prior to concurrent chemo-radiotherapy. Methodology: Patients with LACC and negative para-aortic extensions on the PET/CT were included. Two senior nuclear medicine physicians specialising in gynaecologic oncology reviewed all PET/CT exams, and extracted tumour SUVmax, MTV, and TLG, as well as pelvic lymph node (PLN) involvement. One senior gynecologic oncology pathologist assessed intraepithelial (iTILs) and stromal tumor-infiltrating lymphocytes (sTILs). Results: 86 patients were included in the analysis. High iTILs and sTILs were identified in 29 (34.9%) and 26 (30.2%) patients, respectively. iTILs and sTILs were non significantly associated with tumor metabolic metrics. A high sTILs score was significantly associated with PLN uptake (61.5% compared to 31.7% in low sTILs, p=0.009). Tumors with low iTILs score were significantly associated with a higher magnetic resonance imaging (MRI) tumor size (≥median) (63.3% versus 39.3%, p=0.042). Low iTILs score was also higher in patients with lymph node aortic involvement (14.8% versus 3.4%). Conclusion: Poor or absent iTILs was associated with a more advanced disease at diagnosis, with larger tumor size, and more frequent para-aortic lymph node extension. Intraepithelial and stroma TILs are not redundant and should be assessed separately. Further work is needed to evaluate the association between tumor metabolic profile and immune populations, including different T-cell subtypes.